If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -5y = 13 Solving 6 + -5y = 13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5y = 13 + -6 Combine like terms: 6 + -6 = 0 0 + -5y = 13 + -6 -5y = 13 + -6 Combine like terms: 13 + -6 = 7 -5y = 7 Divide each side by '-5'. y = -1.4 Simplifying y = -1.4
| (10-3)*4-2+1=1 | | 3g+7g=20 | | 91=6t-5 | | 4x-3(-2)=-3 | | 10-3*4(-2+1)=1 | | factorn^2+2n+8=8 | | 3n+9=42 | | 5x+17=52 | | 10(-3*4)-2+1=1 | | n^2+2n+8=8 | | 5x+2.3=1.3 | | 5a-(3a-4)= | | -95=5(y+42) | | 9r=4 | | 6x+22=-4x-(2-4x) | | 8(w+90)+20=-12 | | 2+.10x=10 | | 3(x+3)=7(x-2) | | 10-3*4-(2+1)=1 | | 3.95+.05x=10 | | 8(3x-1)=105 | | 6x^2-x^3-16=0 | | 4w+16= | | 3x-19=-7 | | -13-3v=4(8-3v) | | 1n+17=7 | | 2+.10x=30 | | 5(3x-7)-6(5x-3)=19x | | -1-3v=4(8-3v) | | 6x+96=200 | | 7(z+2)-4=94 | | 66=5t-9 |